(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Gastrointestinal (GI) parasite infections remain a significant health concern in non-human primates, with implications for host fitness, welfare, and zoonotic disease transmission. This study investigated the prevalence, composition, and effects of GI parasites on body weight in a captive colony of Olive Baboons (Papio anubis) at the Kenya Institute of Primate Research (KIPRE). Faecal samples from 52 subjects (11 males and 41 females) were examined using standard parasitological techniques. The overall prevalence of GI parasitic infections was 78.8%, with protozoan infections predominating. Identified parasites included Balantidium spp. (21.2%), Entamoeba spp. (11.5%), and Trichuris trichiura (3.8%), with frequent mixed infections: Balantidium spp. + Entamoeba spp. (32.7%), Balantidium spp. + T. trichiura (3.8%), and Balantidium spp. + Entamoeba spp. + T. trichiura (5.8%). No significant associations were found between infection status and host sex (p = 1.000), age (p = 1.000), or body weight (p = 0.5306). Mean body weights did not differ significantly between infected (15.50 ± 4.79 kg) and non-infected (14.46 ± 4.95 kg) baboons, nor between single (16.10 ± 5.06 kg) and multiple (14.98 ± 4.60 kg) infections. The high infection prevalence indicates constant exposure within the colony; yet stable host condition suggests subclinical infections moderated by adequate care. Continuous monitoring and hygiene management are recommended to sustain primate welfare.